Alterations in drug disposition in older adults: a focus on geriatric syndromes. (2nd January 2021) - Maher, Dorsa; Ailabouni, Nagham; Mangoni, Arduino A.; Wiese, Michael D.; Reeve, Emily
ABSTRACT: Introduction: Age-associated physiological changes can alter the disposition of drugs, however, pathophysiological changes associated with geriatric syndromes in older adults may lead to even greater heterogeneity in pharmacokinetics. Geriatric syndromes are common health problems in older adults which have multifactorial causes and do not fit into distinct organ-based disease categories. With older adults being the greatest users of medications, understanding both age- and geriatric syndrome-related changes is important clinically to ensure safe and effective medication use. Areas covered: This review provides an overview of current evidence regarding pharmacokinetic alterations that occur with aging and in common geriatric syndromes, including frailty, sarcopenia, dementia, polypharmacy and enteral feeding. The evidence is presented according to the four primary pharmacokinetic processes (Absorption, Distribution, Metabolism and Excretion). Expert opinion: There is some evidence to inform our understanding of the impact of chronological aging and various geriatric syndromes on drug disposition. However, many areas require more research, including drug induced inhibition and induction of cytochrome P450 enzymes and the clinical utility of emerging methods for estimating renal function. There is a need to develop tools to predict alterations in drug disposition in subgroups of older adults, particularly where the currently available clinical information is sparse.